Selecting heterozygous parents and single-dose markers for genetic mapping in cassava - Gómez, R.; Angel, F.; Bonierbale, Merideth W.; Rodríguez, F.; Tohme, Joseph M.; Roca, W. (International Center for Tropical Agriculture, 1995)
Random amplified polymorphic DNA (RAPD) analysis was performed on three F1 populations obtained from intraspecific controlled crosses of cassava. Segregation of the RAPD fragments was analyzed to determine if these can serve as genetic markers in cassava for subsequent use in linkage analysis. Seventy primers were evaluated in the largest progeny, and 120 markers were generated; of these, 93 were present in only one parent and 27 were present in both. Polymorphic bands were scored for segregation in the progeny as present or absent. Of the 93 polymorphic markers detected in the largest progeny, 67 segregated 1:1 and 9 showed ratios different to 1:1, indicating that they could be double- or triple-dose with chromatid segregation; 17 showed segregation distortions